Grazing preference and isotopic contributions of kelp to Zostera marina mesograzers - Olson, Angeleen M.; Prentice, Carolyn; Monteith, Zachary L.; VanMaanen, Derek; Juanes, Francis; Hessing-Lewis, Margot (Frontiers in Plant Science, 2022)
In seagrass food webs, small invertebrate mesograzers often exert top-down control on algal epiphytes growing on seagrass blades, which in turn releases the seagrass from competition for light and nutrients. Yet, nearshore habitat boundaries are permeable, and allochthonous subsidies can provide alternative food sources to in-situ production in seagrass meadows, which may in turn alter mesograzer-epiphyte interactions. We examined the contribution of allochthonous kelp (Nereocystis luetkeana), autochthonous epiphytic macroalgal (Smithora naiadum), Ulva lactuca, and seagrass production to mesograzer diets in a subtidal Zostera marina (eelgrass) meadow. In both choice feeding experiments and isotopic analysis, mesograzer diets revealed a preference for allochthonous N. luetkeana over Z. marina, S. naiadum, and U. lactuca. Notably, Idotea resecata showed an ~8x greater consumption rate for N. luetkeana in feeding experiments over other macrophytes. In the meadow, we found a positive relationship between epiphytic S. naiadum and gammarid amphipod biomass suggesting weak top-down control on the S. naiadum biomass. Epiphyte biomass may be driven by bottom-up factors such as environmental conditions, or the availability and preference of allochthonous kelp, though further work is needed to disentangle these interactions. Additionally, we found that gammarid and caprellid amphipod biomass were positively influenced by adjacency to kelp at seagrass meadow edges. Our findings suggest that N. luetkeana kelp subsidies are important to the diets of mesograzers in Z. marina meadows. Spatial planning and management of marine areas should consider trophic linkages between kelp and eelgrass habitats as a critical seascape feature if the goal is to conserve nearshore food web structure and function.